Distribution and Growth in an Economy with Limited Needs - Gilles Saint-Paul (Institute for the Study of Labor (IZA), 2001)
This paper studies a model of the distribution of income under bounded needs. Utility derived from any given good reaches a bliss point at a finite consumption level of that good. On the other hand, introducing new varieties always increases utility. It is assumed that each variety is owned by a monopoly. Workers can specialize in material goods production or in the knowledge sector, which designs new varieties. It is shown that if the elasticity of labor supply to the knowledge sector is bounded, as productivity increases, the economy moves from a ?Solovian zone? where wages increase with productivity, to a ?Marxian? zone where the paradoxically decline with productivity. This is because as consumption of a given good increases, the price elasticity of demand falls, and markups increase to infinity as consumption reaches the unit elasticity point. Such a point typically exists because of the finiteness of needs. It is also shown that if individual creativity is more unevenly distributed then productivity, technical progress always increases inequality. Redistribution from profits to workers in the production sector always benefits arbitrarily poor workers regardless of their distortionary effect on the number of varieties, because diversity is not valued by very poor agents. In contrast, rich agents close enough to their bliss point can only be made better-off by an increase in diversity. If wages are set by monopoly unions rather than set competitively, they are proportional to productivity and the Marxian zone no longer exists. But technical progress always reduces employment in the material goods sector. International trade may reduce wages in poor countries and increase them in rich countries if under autarky the former consume less of each good that the latter.
Keywords: D42; E11; O14; E24; F15; D3; O15; J31; E25; L12; O3; O41; F12; 330; Income distribution; innovation; knowledge economy; economic growth; technical change; wages; Research and Development; Verteilungstheorie; Neue Wachstumstheorie; Mehr-Sektoren-Modell; Technischer Fortschritt; Produktivität; Lohn; Grenznutzentheorie; Mehrwerttheorie; Steady-State-Wachstum; Monopol; Offene Volkswirtschaft; Theorie